Нормативно-правове регулювання питань здійснення процедур митного контролю та митного оформлення водних транспортних засобів і товарів, що переміщуються ними - Руда, Т. В.; Артеменко, А. В.; Ruda, Т.; Artemenko, А. (ЦНТУ, 2017)
У статті розкрито основні аспекти нормативно-правового регулювання питань здійснення процедур митного контролю та митного оформлення водних транспортних засобів і товарів, що переміщуються ними. Зокрема, досліджено митні формальності на морському і річковому транспорті, особливості митного оформлення суден закордонного плавання та специфіку пропуску через митний кордон рибної продукції. Проаналізовано Технологічну схему здійснення митного контролю водних транспортних засобів перевізників і товарів, що переміщуються ними у пунктах пропуску через державний кордон. Окреслено сутність та особливості функціонування інформаційної системи портового співтовариства. Наведено характеристику Порядку використання митних формальностей на морському та річковому транспорті. Окреслено особливості надання та опрацювання попередньої інформації при здійснення процедур митного контролю та митного оформлення водних транспортних засобів і товарів, що переміщуються ними. The object of the article is analysis of Normative and Legal regulation of issues of implementing of Procedures of Customs Control and Customs Formalities of water vehicles and goods which are transported by them. The main aspects of Normative and Legal regulation of issues of implementing of Procedures of Customs Control and Customs Formalities of water vehicles and goods which are transported by them are opened in the article. Particularly, Customs Formalities on sea and river vehicles, features of Customs Clearance of foreign voyage vessels and specificity of passage of fish products through the customs border are researched. The Technological Scheme of implementing of Customs Control of water vehicles of carriers and goods which are transported by them in Check Points on State Border is analyzed. The essence and features of functioning of Ports Community Information System are outlined. The characteristic of Order of implementing of Customs Formalities on sea and river vehicles is presented. Features of giving and processing of pre-information in the process of implementing of procedures of Customs Control and Customs Clearance of water vehicles and goods which are transported by them are outlined. Results of the research showed that the features of Normative and Legal regulation of issues of implementing of Procedures of Customs Control and Customs Formalities of water vehicles and goods which are transported by them are: International Agreements are wide used in this field; customary rules are used more often in this fields, than in other fields; activity of sea vehicles is related with passage of a lot of cargo and this issue has be included in the process of development and using of appropriate normative acts. Besides, it is necessary to emphasize that the Normative and Legal base on implementing of Procedures of Customs Control and Customs Formalities of water vehicles and goods which are transported by them needs to be a little bit improved. In particularly, the issues on automation of Customs Procedures on water vehicles have to be concretized. The necessity to use the Ports Community Information System is a very relevant today, but at the same moment, the implementing of Customs Procedures without using of Ports Community Information System is described too. The process of integration of Program and Information Complexes which are developed by State Fiscal Service is disorderly. There are no unified requirements to giving of preinformation with using of Ports Community Information System and without using of it. The issues on integration of Ports Community Information System into Program and Information Complexes which are developed by State Fiscal Service needs essential improving.
Normative and legal regulation of issues of implementing of procedures of customs control and customs formalities of water vehicles and goods which are transported by them
Keywords: нормативно-правове регулювання; митний контроль та митне оформлення водних транспортних засобів і товарів; митні формальності на морському і річковому транспорті; інформаційна система портового співтовариства; legal regulation; customs control and customs clearance of water vehicles and goods moving by them; customs formalities on sea and river transport; information system of the port community